Relationship between self-efficacy and academic motivation among nursing students - Shrestha, Sandhya; Tuladhar, Jyoti Badan (Journal of Chitwan Medical College, 2021)
Background: Self-efficacy and academic motivation are both essential component for nursing profession which have a direct influence on academic success therefore this study aimed to investigate the relationship between Self-efficacy and Academic motivation among Nursing Students of Nepal. Methods: A cross-sectional study was conducted among 203 Proficiency Certificate Level and Bachelor of Science in nursing students of, Pokhara, Nepal during February 2020. Self -administered Demographic Performa, Jerusalem and Schwarzer Self-efficacy, Modified vallerend Academic motivation was used for data collection. Data were analyzed using Descriptive statistics and inferential statistics. Results: The study revealed among 203 nursing students. Majority (76.5%) were from age group 16-25 years, mean age was 18.96 ± 1.96, majority (82.8%) were Hindu. Most of all (98.0%) were unmarried, majority (85.7%) were from nuclear family. More than half (57.1%) were from proficiency certificate level student, one third (31.5%) were from third year. The mean self-efficacy score was 30.22±4.2 and mean total academic motivation was 95.19±13.71. Conclusions: Study findings showed that majority of nursing students have average level of self -efficacy and average level of academic motivation. Self- efficacy was significantly correlated with academic motivation so that nurse educators should help to boost self- efficacy.